Particle-based methods fundamentals and applications - Oñate, E.; Owen, D. R. J.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This book contains 11 chapters written by relevant scientists in the field of particle-based methods and their applications in engineering and applied sciences. The chapters cover most particle-based techniques used in practice including the discrete element method, the smooth particle hydrodynamic method and the particle finite element method. The book will be of interest to researchers and engineers interested in the fundamentals of particle-based methods and their applications.
Advances in the Particle Finite Element Method (PFEM) for solving coupled problems in engineering -- Advances in Computational Modelling of Multi-Physics in Particle-Fluid Systems -- Large Scale Simulation of Industrial, Engineering and Geophysical Flows Using Particle Methods -- Parallel computation particle methods for multi-phase fluid flow with application oil reservoir characterization -- The Particle Finite Element Method for multi-fluid flows -- On Material Modeling by Polygonal Discrete Elements,- Discrete numerical analysis of failure modes in granular materials -- Homogenization of Granular Material modelled by a 3D DEM -- Some consideration on derivative approximation of particle methods -- Discrete element modelling of rock cutting.
Electronic reproduction.
Keywords: Particle methods (Numerical analysis); Electronic books